1990
DOI: 10.1007/bf00280054
|View full text |Cite
|
Sign up to set email alerts
|

Variation of benzbromarone elimination in man — a population study

Abstract: The plasma benzbromarone concentration-time profile in a healthy subject who retained the compound much longer than other individuals is described. The data suggested that determination of the 24 h plasma concentration of the parent drug after a single oral dose of 100 mg benzbromarone would be an appropriate procedure to determine the elimination phenotype. Based on this procedure, 148 of 153 healthy individuals (97%) in a population study were found to eliminate benzbromarone rapidly. In one subject the 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Therefore, we intended to maintain low and stable urate levels based on benzbromarone pharmacokinetics. This uricosuric agent is usually prescribed once daily because its metabolites have a half-life of 17–20 h [22, 23]. However, the peak action of this medication occurs within 4 hours following intake.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we intended to maintain low and stable urate levels based on benzbromarone pharmacokinetics. This uricosuric agent is usually prescribed once daily because its metabolites have a half-life of 17–20 h [22, 23]. However, the peak action of this medication occurs within 4 hours following intake.…”
Section: Discussionmentioning
confidence: 99%
“…BBR undergoes hepatic hydroxylation to 1′-hydroxy BBR and 6-hydroxy BBR. The BBR elimination in serum was affected by genetic polymorphism in drug metabolism [71]. It was demonstrated that CYP2C9 was the main enzyme responsible for the 6-hydroxylation of BBR [72,73].…”
Section: The Genes That Influence Uricosuricsmentioning
confidence: 99%
“…Plasma concentrations and renal excretion of uric acid also were determined to establish possible correlations between drug plasma levels and uric acid metabolism, as reported previously [9]. In an earlier epidemiological [25] and in a family study [22] one of the volunteers included in the present investigation was found to be a slow eliminator of Bzbr, as determined by a single benzbromarone plasma concentration 24 h after drug administration.…”
Section: Abstract: Benzbromarone Metabolism -Slow Elimination Phenotmentioning
confidence: 99%
“…Recently further metabolites of Bzbr have been characterized by gas chromatography -mass spectrometry in plasma after drug administration to humans [5,6] and in-vitro after incubation of Bzbr with human and rat liver microsomes [22,23]. In addition from the already known metabolites M1 and M2, further minor metabolites have been detected and characterized by gas chromatographymass spectrometry derivatization: metabolites M3, (l'-keto-Bzbr), M 4 (2'-hydroxybenzbromarone, an isomer of M0; M 5 (l',6-dihydroxybenzbromarone), M 6 (dihydroxy-aryl-benzbromarone), and M 7 and M 8 (isomers of M2) were detectable in all samples, although in different ratios.…”
Section: Metabolite Mmentioning
confidence: 99%